Family Stigma: A Concept Analysis - Sihyun Park, PhDc, RN; Kyung Sook Park, PhD, RN (Elsevier, 2014)
Purpose: Stigma negatively affects individuals as well as entire families; therefore, it is necessary to understand "family stigma" in order to reduce the social and emotional distress of families suffering from stigma and prevent the resulting avoidance of social support and treatment. Thus, this study clarifies the concept of "family stigma" by using concept analysis method. Methods: In order to analyze the concept, we reviewed the relevant literatures. Characteristics that appeared repeatedly throughout the literature were noted and categorized. Results: Three key defining attributes were identified: (a) others' negative perceptions, attitudes, emotions, and avoidant behaviors toward a family, because of the unusualness of the family, including the negative situations, events, behaviors, problems or diseases associated with that family, or because of the unordinary characteristics or structures of that family; (b) others' belief that the unusualness of the family is somehow harmful, dangerous, unhealthy, capable of affecting them negatively, or different from general social norms; and (c) others' belief that the family members are directly or indirectly contaminated by the problematic family member, so that every family member is also considered as harmful, dangerous, unhealthy, capable of having a negative effect on others, or different from general social norms. Conclusion: The results of this study are expected not only to guide future research but also to enhance family care in nursing practice.